Aflatoxin B1 modulates the expression of phenotypic markers and cytokines by splenic lymphocytes of male F344 rats. Issue 3 (19th March 2013) - Qian, Guoqing; Tang, Lili; Guo, Xia; Wang, Franklin; Massey, Michael E.; Su, Jianjia; Guo, Tai L.; Williams, Jonathan H.; Phillips, Timothy D.; Wang, Jia‐Sheng
ABSTRACT Aflatoxin B1 (AFB1) is immunotoxic to animals and a suspected immunosuppressant in humans. In this study, we investigated the effects of AFB1 on splenic lymphocyte phenotypes and the inflammatory cytokine expression in male F344 rats. Exposure of animals to AFB1 [5–75 µg kg–1 body weight (BW)] for 1 week showed dose‐dependent decreases in the percentage of splenic CD8+ T cells and CD3‐CD8a+ NK cells. A general inhibition of the expression of interleukin (IL)‐4 and interferon (IFN)‐γ by CD4+ T cells, IL‐4 and IFN‐γ by CD8a+ cells, and tumor necrosis factor (TNF)‐α expression by natural killer (NK) cells was also found; however, no concurrent histological changes in spleen tissue were present, suggesting acute immunosuppression without overt toxicity. Five‐week exposure with AFB1 significantly increased the percentages of CD3+ and CD8+ T cells, especially at low doses (≤ 25 µg kg–1). AFB1 treatment significantly decreased the anti‐inflammatory cytokine IL‐4 expression by CD4+ T cells and significantly increased the pro‐inflammatory cytokine IFN‐γ expression by CD4+ T cells and TNF‐α expression by NK cells. These results indicated that repeated AFB1 exposure promotes inflammatory responses by regulating cytokine expression. Our data provides novel insights into the mechanisms by which AFB1 exposure differentially modulates the cell‐mediated immune responses and suggests the involvement of an inflammatory response upon repeated exposure. Copyright © 2013 John Wiley & Sons, Ltd.